(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The main principles of designing maps and categories of reclamation status of the Republic of Karakalpakstan it is considered in the areas of the Ustyurt Plain and the Aral Sea using GIS technologies. Geolocation and map analysis features, additional maps are provided explanations, as well as land reclamation in the Ustyurt plain, relief forms, the Republic of Karakalpakstan, the example of Muynak district in the Aral sea region. Information about underground water, i.e. natural geographical description of the area. This article is about the analysis of the changes in the environmental reclamation condition of the soil in the territory of the Republic of Karakalpakstan and the methods of soil mapping and the Ustyurt Plain and the southern Aral Sea the analysis data of the cartographic images based on the ecological situation in the area is presented.